Rapid BMI Increases and Persistent Obesity in Small-for-Gestational-Age Infants - Wu, Dan; Zhu, Jianzheng; Wang, Xiulian; Shi, Huiqing; Huo, Yanyan; Liu, Meiyan; Sun, Fanfan; Lan, Hongyan; Guo, Chong; Liu, Honghua; Li, Tingting; Jiang, Lian; et al. (Frontiers in Pediatrics, 2021)
Purpose: In order to compensate for the early intrauterine growth restriction, small-for-gestational age (SGA) infants have "catch-up growth" after birth. Increased caloric intake has been suggested for SGA infants and it is important to determine if the early growth rate of body mass index (BMI) is associated with risk of persistent obesity later in life. In this longitudinal cohort study, we assessed the BMI of a large cohort of children who were SGA at birth to determine their risk of persistent obesity at school going age (6-7 years) due to excessive weight gain in the first three years of life. Methods: We collected the height and weight data of 23,871 SGA babies. A polynomial function was used to fit the BMI-for-age z-score (BAZ) values of 0-6 years old SGA children and simulate their growth trajectory. In addition, we screened out 6,959 children from 23,871 children to further evaluate the dynamic changes of early childhood BMI. We divided the school-age children into groups as non-obese (BAZ<2) and obese (BAZ > 2), and determined the association between changes in BMI and the risk of school-age obesity. We also analyzed the association between length of breast feed and risk of obesity. Results: From the perspective of BMI distribution, the simulated growth trajectory indicated that SGA children reaching overweight/obese levels in early childhood, remained obese until school age (R2，O.65；R2，O.21).The retrospective analysis showed that children who were overweight and obese during school age had a high BMI from early age. By analyzing the changes in early BMI, we found that the fastest growth rate of SGA children occurred in the early infancy before 6 months and continued to grow rapidly for a period of time. Interestingly, pre-SGA children who maintained a near overweight (1